Integration of photosynthetic pigment-protein complexes in dye sensitized solar cells towards plasmonic-enhanced biophotovoltaics - Yang, Yiqun (Kansas State University, 2016)
Solar energy as a sustainable resource is a promising alternative to fossil fuels to solve the tremendous global energy crisis. Development of three generation of solar cells has promoted the best sunlight to electricity conversion efficiency above 40%. However, the most efficient solar cells rely on expensive nonsustainable raw materials in device fabrication. There is a trend to develop cost-effective biophotovoltaics that combines natural photosynthetic systems into artificial energy conversion devices such as dye sensitized solar cells (DSSCs). In this research, a model system employs natural extract light-harvesting complex II (LHCII) as a light-absorbing sensitizer to interface with semiconductive TiO₂ and plasmonic nanoparticles in DSSCs. The goal of this research is to understand the fundamental photon capture, energy transfer and charge separation processes of photosynthetic pigment-protein complexes along with improving biophotovoltaic performance based on this model system through tailoring engineering of TiO₂ nanostructures, attaching of the complexes, and incorporating plasmonic enhancement. The first study reports a novel approach to linking the spectroscopic properties of nanostructured LHCII with the photovoltaic performance of LHCII-sensitized solar cells (LSSCs). The aggregation allowed reorganization between individual trimers which dramatically increased the photocurrent, correlating well with the formation of charge-transfer (CT) states observed by absorption and fluorescence spectroscopy. The assembled solar cells demonstrated remarkable stability in both aqueous buffer and acetonitrile electrolytes over 30 days after LHCII being electrostatically immobilized on amine-functionalized TiO₂ surface. The motivation of the second study is to get insights into the plasmonic effects on the nature of energy/charge transfer processes at the interface of photosynthetic protein complexes and artificial photovoltaic materials. Three types of core-shell (metal@TiO₂) plasmonic nanoparticles (PNPs) were conjugated with LHCII trimers to form hybrid systems and incorporated into a DSSC platform built on a unique open three-dimensional (3D) photoanode consisting of TiO₂ nanotrees. Enhanced photon harvesting capability, more efficient energy transfer and charge separation at the LHCII/TiO₂ interface were confirmed in the LHCII-PNP hybrids, as revealed by spectroscopic and photovoltaic measurements, demonstrating that interfacing photosynthesis systems with specific artificial materials is a promising approach for high-performance biosolar cells. Furthermore, the final study reveals the mechanism of hot electron injection by employing a mesoporous core-shell (Au@TiO₂) network as a bridge material on a micro-gap electrode to conduct electricity under illumination and comparing the photoconductance to the photovolatic properties of the same material as photoanodes in DSSCs. Based on the correlation of the enhancements in photoconductance and photovoltaics, the contribution of hot electrons was deconvoluted from the plasmonic near-field effects.
Keywords: Dye sensitized solar cell; Plasmonic enhancement; Biophotovoltaics; Hot electron injection; Light harvesting complex; Core-shell nanoparticles